The relationship between work life balance and job satisfaction among career women in hotel industry in Kuala Terengganu - Hilman Hajijan
The objective of carrying out this research is to study the relationship between work life balance and job satisfaction among career women in hotel industry in Kuala Terengganu. The elements of work domain that may impact job satisfaction include work place culture, social support, work-life balance and motivation. The correlation between work life balance and job satisfaction of female employees had been discussed in this research. The focus of this study is on the women employees who work in hotels in the district of Kuala Terengganu, Terengganu. In this research, a total of 300 questionnaires had been circulated and 210 of them had been returned successfully. The researcher adapted Statistical Analysis ystern Enterprise Guide (SAS) Version 7.l to analyze the data where Pearson Correlation Coefficient Analysis and Multiple Regression Analysis are inculcated to determine the relationship between the independent variables (work place culture, social support, work-life balance, and motivation) and dependent variable (job satisfaction). At the end, both independent variables (work place culture, social support, work-life balance, and motivation) and dependent variable (job satisfaction) are found to have a positive significant relationship with the dependent variable (job satisfaction). Lastly, a summary on the findings, research implication, research limitation and some recommendations are discussed in this study.